2021
DOI: 10.1002/hbm.25563
|View full text |Cite
|
Sign up to set email alerts
|

Visual experience modulates whole‐brain connectivity dynamics: A resting‐state fMRI study using the model of radiologists

Abstract: Visual expertise refers to proficiency in visual recognition. It is attributed to accumulated visual experience in a specific domain and manifests in widespread neural activities that extend well beyond the visual cortex to multiple high‐level brain areas. An extensive body of studies has centered on the neural mechanisms underlying a distinctive domain of visual expertise, while few studies elucidated how visual experience modulates resting‐state whole‐brain connectivity dynamics. The current study bridged th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 103 publications
(151 reference statements)
0
9
0
Order By: Relevance
“…Visual expertise is a cognitive process that involves visual object recognition ability in a specific domain, resulting in superior visual object recognition performance (Harel, 2016 ; Wang et al, 2021 ). The development of visual expertise is thought to involve reciprocal interactions between the visual system and multiple high-level areas across the brain (Harel, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual expertise is a cognitive process that involves visual object recognition ability in a specific domain, resulting in superior visual object recognition performance (Harel, 2016 ; Wang et al, 2021 ). The development of visual expertise is thought to involve reciprocal interactions between the visual system and multiple high-level areas across the brain (Harel, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was supported by Bilalic et al ( 2016 ) who showed that FFA could help radiologists discriminate X-ray stimuli from other stimuli and then contribute to the evaluation of radiographic images. Lastly, Wang et al ( 2021 ) proposed that visual experience could modulate the functional adaptation of the visual cortex and other cognitive areas that are responsible for decision making, semantic knowledge, and attention, as evidenced by widely altered functional connectivity in the entire cortex including the SFG, MFG, orbitofrontal cortex (OFC), and fusiform gyrus (FuG). Collectively, these studies suggest that the activation of these circuits or brain areas constitutes a cortical organizing principle of visual expertise in the brain, such as visual processing, attention control, decision making, and semantic memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we used questionnaires to ensure that the subjects had no visual expertise of other known domains, such as aircrafts, animals, and plants. The behavioral tasks were conducted after MRI scanning, aiming to quantify the level of face expertise and radiological expertise, using the Cambridge face memory test (CFMT) ( Duchaine and Nakayama, 2006 ) and radiological expertise task ( Evans et al, 2011 ) respectively, as introduced in our previous studies ( Wang et al, 2021 ; Zhang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among all the issues related to resting state spontaneous neuronal activity, the baseline brain activity is of particular significance. The baseline spontaneous neuronal activity reflects cortical excitability [ 21 , 31 ], the alteration of which influences the strength of connection and connectomes-based analysis in resting fMRI studies [ 32 , 33 ], as well as pattern of the spatial activation under task [ 34 , 35 ]. Previous studies used the amplitude of low-frequency (< 0.08 Hz) fluctuation (ALFF) as the metric of brain intrinsic activity [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%